Case Series Investigating the Efficacy and Safety of Bilateral Fluocinolone Acetonide (ILUVIEN®) in Patients with Diabetic Macular Edema. Issue 1 (June 2016) - Elaraoud, Ibrahim; Attawan, Alaa; Quhill, Fahd
Abstract Introduction Patients with diabetic macular edema (DME), a chronic, vision-limiting condition, may be insufficiently responsive to standard-of-care anti-vascular endothelial growth factor (VEGF) and/or laser therapies. One approved treatment for such patients is 0.2 μg/day fluocinolone acetonide (FAc) sustained-release implant; however, data are limited for treatment strategies in patients with bilateral chronic DME insufficiently responsive to standard-of-care therapies. Methods Six pseudophakic patients with bilateral, chronic DME previously treated with laser and anti-VEGF therapy (and intravitreal triamcinolone acetonide in 10 eyes) were retrospectively investigated for visual and anatomical outcomes, 6 months post-0.2 μg/day FAc implant in both eyes. Results At baseline, the mean best corrected visual acuity (BCVA) was approximately 6/38 or 43 [standard deviation (SD) ±17.4] Early Treatment Diabetic Retinopathy Study (ETDRS) letters; mean central retinal thickness (CRT) was 648 μm (SD ±160). Mean change in BCVA was +10 letters (SD ±12.2 letters), with 4/12 eyes maintaining or achieving driving vision (≥70 letters) and 3/12 eyes having unchanged BCVA. CRT was reduced 6 months after 0.2 μg/day FAc implant in 11/12 eyes. The mean intraocular pressure (IOP) was 16.1 mmHg [mean change of 1.1 mmHg (SD ±3.6)]. Conclusion In a real-world setting, 0.2 μg/day FAc implant in both eyes was a feasible, effective choice for patients with severe bilateral DME, without notable increases in IOP. Funding Publication charges were funded by Alimera Sciences Ltd. Medical writing assistance for this study was provided by QXV Communications and funded by Alimera Sciences Ltd.